A Simple Method for Percutaneous Reduction of Isolated Zygomatic Arch Fractures With a Dental Elevator: A Technical Note. (2nd September 2020) - Sorghabi, Wais; Kleinbergen, Jurrijn; Bos, Ruud; Van Minnen, Baucke
Isolated zygomatic arch fractures are common fractures of the facial skeleton. Dislocation may result in facial disharmony and/or restricted mouth opening if not treated properly. Different methods of minimally invasive treatment of depressed fractures of the zygomatic arch have been described. Most of them are based on either a direct percutaneous approach with a malar hook, a temporal approach according to Gillies, or transorally according to Keen. For these methods, general anesthesia is often preferred. In this technical note, an alternative method of a percutaneous approach for reduction of a zygomatic arch fracture under local anesthesia is presented.